Kerberos System Based Security Model Using Two Factor Authentication for Cloud Computing - Kim, Young-Soo; Yup Lee, Byoung (International Journal of Engineering and Technology, 2018)
Background/Objectives: The authentication technology is important in the cloud environment where many users and data are mixed. Therefore, we suggest a Kerberos-based Two Factor Authentication model to address the vulnerability of password.Methods/Statistical analysis: We design and implement our suggested model. To check the practicality of cloud computing security model adopting Kerberos system based authentication model and Two Factor Authentication, we materialized authentication security model and authorization model.Findings: In order to decrease the vulnerability of the password, we suggests Kerberos system based Two Factor Authentication model. We found that the suggested model has no errors in running, ensures security and confidentiality of information of the user when applied to the cloud environment to prevent cyber attacks targeting cloud services,and is resistant to cloud server attack by an attacker so that it can be the solution.Improvements/Applications: Our suggested model ensures the security and confidentiality of information of a user when applied to the cloud that underlies a variety of application fields such as big data so that it can prevent cyber attacks targeting cloud services and contribute to activation of cloud computing.Â